The concept of the lived world : an introduction to the phenomenology of Merleau-Ponty - Wait, Eldon Christopher (Department of Philosophy, 2016)
The task we have set ourselves in this thesis is not to interpret or translate Merleau-Ponty's expressions but rather to re-create his philosophy, avoiding as far as possible the actual expressions he used, not because we find any fault with them but because we wish to re-create the conditions under which they can appear in their original urgency and vitality. We must understand Merleau-Ponty by being present at the birth of his philosophy, to experience the philosophy "from the inside" Our approach must be distinguished from a purely historical or a phychological one. We do not wish to introduce the thought of Merleau-Ponty by an examination of pre-phenomenological thought, nor do we wish to concern ourselves with his personal development which led to the writing of "The Phenomenology of Perception". Our approach is phenomenological. We wish to understand Merleau-Ponty's existential phenomenology as itself an intentional movement, as the "coming about" of the structure of intentionality, or as we will refer to it, the coming about of the imperfect unity, or the informal essence. Our discussions of the psychological ego and the transcendental ego are important not only as an historical introduction, but because psychologism and transcendentalism are respectively the noetic and noematic poles of this intentional movement.